Práticas educomunicativas para inclusão do cidadão à previdência social brasileira - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This article deals with theoretical research on Educommunication, actions for the inclusion of citizens in Social Security and the Social Security Education Program of the National Institute of Social Security - PEP/INSS. It is proposed to bring together the theory and practices of Educommunication with the Social Security Education Program/INSS. Educommunication understood as a communication practice to develop citizenship, social inclusion, access to information, critical reading of information and the use of information for the emancipation of citizens. This research has as its premise, therefore, to carry out a theoretical and practical reading, identifying paths pointed out by Educommunication that can be applied in the Social Security Education Program of the INSS. This study identified methods and procedures to be adopted so that information reaches citizens in a clear, inclusive and emancipating way so that they know their rights. Therefore, it is clear that it is fundamental to carry out the identification and mapping of the subjects who are the target of the program's actions, aiming to promote actions with specific guidelines and a focus on digital inclusion. Social inclusion actions on welfare benefits with a focus on information about rights, partnerships to develop digital inclusion actions, and also expand social security information multipliers.
Keywords: Comunicação de massa e educação; Democracia - Participação do cidadão; Previdência social; Instituto Nacional do Seguro Social (Brasil); Mass communication and education; Democracy - Citizen Participation; CNPQ::CIENCIAS SOCIAIS APLICADAS